Forecasting demand for long-term care based on multistate piecewise constant Markov process - Cui Xiaodong; Zheng Yuhua (Universitas Islam Indonesia, 2018)
This paper forecasts demand for long-term care based on multistate piecewiseconstant Markov process. Two types of data are mainly used in this study. Thefirst type of data came from the Chinese Longitudinal Healthy Longevity Survey(CLHLS), 2008-2011. The second type of data came from the China’sDemographic Yearbook of 2016, used as the number of population in the baseperiod. It finds that the changes in health have a significant difference in genderand age. It also finds that under different health states, the distribution of durationof staying in each state in different gender and age groups shows a characteristicsimilar to the distribution of population size.